Oxidation by 2-oxoglutarate oxygenases: non-haem iron systems in catalysis and signalling. - Hewitson, K; Granatino, N; Welford, R; McDonough, M; Schofield, C (2005)
The 2-oxoglutarate (2OG) and ferrous iron dependent oxygenases are a superfamily of enzymes that catalyse a wide range of reactions including hydroxylations, desaturations and oxidative ring closures. Recently, it has been discovered that they act as sensors in the hypoxic response in humans and other animals. Substrate oxidation is coupled to conversion of 2OG to succinate and carbon dioxide. Kinetic, spectroscopic and structural studies are consistent with a consensus mechanism in which ordered binding of (co)substrates enables control of reactive intermediates. Binding of the substrate to the active site triggers the enzyme for ligation of dioxygen to the metal. Oxidative decarboxylation of 2OG then generates the ferryl species thought to mediate substrate oxidation. Structural studies reveal a conserved double-stranded beta-helix core responsible for binding the iron, via a 2His-1carboxylate motif and the 2OG side chain. The rigidity of this core contrasts with the conformational flexibility of surrounding regions that are involved in binding the substrate. Here we discuss the roles of 2OG oxygenases in terms of the generic structural and mechanistic features that render the 2OG oxygenases suited for their functions.